Analisis Perputaran Persediaan pada Ultra Jaya Milk Industry & Trading Company Tbk yang Terdaftar di Bursa Efek Indonesia - Trinoviyanti (LANCAH: Jurnal Inovasi dan Tren, 2024)
This research aims to analyze the turnover of receivables in food and beverage companies listed on the Indonesia Stock Exchange (BEI) during the period 2020 to 2023. The data used in this research comes from 2020 to 2023 which is available on the IDX. Data analysis uses quantitative descriptive methods to measure the level of accounts receivable turnover. The company sampled in this research is Ultra Jaya Milk Industry & Trading Company Tbk, using financial reports, namely balance sheets and profit and loss reports for the 2020-2023 period. The results of the analysis show that the inventory turnover ratio in 2020 is 2.55 times, indicating that the company is able to collect its inventory about 2.55 times a year. In 2021, the inventory turnover ratio increased to 3.43 times, indicating increased efficiency in inventory management. The year 2022 shows a movement in the inventory turnover ratio of 3.06 times, indicating consistency in the company's inventory management. However, in 2023, the inventory turnover ratio will decrease to 2.47 times, reflecting a decrease in the average inventory owned by the company. This study provides insight into the effectiveness of Ultra Jaya Milk Industry & Trading Company Tbk's inventory management strategies during the period investigated.